Determination of zinc speciation in soil using synchrotron radiation and its effects on cellular organelles of Phragmites australis. Issue 1 (1st April 2022) - Minkina, Tatiana; Nevidomskaya, Dina; Fedorenko, Grigoriy; Fedorenko, Aleksei; Rajput, Vishnu D.; Shuvaeva, Victoria; Tsitsuashvili, Victoria; Chaplygin, Victor; Rajput, Priyadarshani
Abstract: It is necessary to apply modern approaches to prevent the spread/toxic effects of pollution caused by a changing climate; especially metal pollutants to the soil. Thus, the present investigation was aimed to examine chemical speciation of soil samples collected from the River floodplain and its effects on native plant species; Phragmites australis . Synchrotron radiation (SR) tools for Zn speciation in soil and scanning electron microscopy for anatomical changes in plants were applied. Speciation of Zn was a dominant pollutant in Technosols. Two local surroundings were observed for Zn corresponding to its coordination by O and by S, close to ZnS. Whereas, the mixed local surrounding was noted with Zn–S and Zn–O bonds. The analysis of X-ray absorption fine structure results revealed that Technosols contained 70 and 30% of Zn–S and Zn–O bonds, respectively. SR results could be summarized that the main contribution in Technosols was from the authigenic minerals of metals with S: würtzite (hexagonal ZnS), sphalerite (cubic ZnS), bornite (Cu5 FeS4 ), and covellite (CuS). The investigation on growth and modifications in the ultrastructure of P. australis roots and stems showed changes in cellular tissues such as in epidermis and mesoderm, and in subcellular organelles: mitochondria, chloroplast, cell membrane, etc. It is established that the soil contamination with exceeded limits slows down the ontogenetic developments of P. australis . Our findings could provide insight into the physiochemical characteristics of polluted soil as well as information on the toxic effects of pollutants on plants based on non-destructive approaches.